Exploring the Interplay of Faith and Experience: Religious Sensibility in Kamala Das’s Poetry - Majumder, Rajib (International Journal of Applied and Scientific Research, 2024)
The key elements in the discussed text revolve around religious sensibility, faith, and experience, particularly within the context of Kamala Das's writings. The exploration into Das's works highlights the intricate interrelationship between faith and experience, portraying a dynamic journey where faith both emerges from and shapes the self. The nuanced depiction of religious sensibility underscores the complexity of this relationship. Kamala Das's narratives, spanning childhood encounters with deities to introspective moments of ecstasy, provide a multifaceted examination of these themes. The convergence of religious awareness, personal experiences, and transformative faith contributes to the richness of Das's literary legacy, offering readers profound insights into the complexities of spirituality and self-awareness.